Deep drawing of tailor-welded blanks made of high-strength steel - Schrek, Alexander; Švec, Pavol; Gajdošová, Veronika (Advances in Mechanical and Materials Engineering, 2016)
A comparison study was conducted to evaluate the deep drawing of a rectangular box from tailor-welded blank, composed of two parts of different thicknesses. The blank material is high strength steel with transformation induced plasticity, and the weld line is located in the blank centre at the beginning of the deep drawing. The study is focused on the weld line movement during the deep drawing with quasi uniform or controlled non-uniform distribution of the blankholder pressure, which is applied on the flange of the blank. The goal is to minimise the weld line movement and to improve the formability of the tailor-welded blank.